Birdsong [book with audioplayer] - Flett, Julie ([Library Ideas, LLC], 2022)
A tender, luminous portrait of art, nature, and connecting across generations. When a young girl moves from the country to a small town, she feels lonely and out of place. But soon she meets an elderly woman next door, who shares her love of arts and crafts. Can the girl navigate the changing seasons and failing health of her new friend? Acclaimed author and artist Julie Flett's textured images of birds, flowers, art, and landscapes bring vibrancy and warmth to this powerful story, which highlights the fulfillment of intergenerational relationships and shared passions.